DEVELOPMENT OF INTERCULTURAL COMMUNICATION IN THE PROCESS OF LEARNING (Web of Teachers: Inderscience Research, 2024)
In this article, the author emphasizes the importance of intercultural communication in society. The author believes that the culture of each nation is diverse and valuable in its own way. The article provides methods for developing intercultural communication based on the study of a foreign language.